Novel finding: Hyo-mandibular ligament- A cadaveric study - Meghan Neill; Haley Nation (Wolters Kluwer Medknow Publications, 2023)
Background: Many anatomical variations have been described in the deep neck; several of these are associated with the hyolarynx complex, consisting of the styloid process, hyoid bone, stylohyoid ligament, and thyroid, cricoid, and arytenoid cartilages as well as their associated ligaments. Methodology: An anterolateral deep dissection of the neck was performed bilaterally in 37 donors. Results: A novel ligament was found to connect the lesser horns of the hyoid bone to the angle of the mandible bilaterally in seven body donors (a total of 14 sides). To the best of our knowledge, the presence or function of a ligament connecting the lesser horns of the hyoid bone to the mandible has never been previously described or reported. Due to its proximal and distal attachment sites, we have termed this finding a "hyomandibular ligament." Conclusion: This unique finding is clinically relevant and may add insight into the structural and functional variations of the deep neck. Knowledge of this structure and similar anatomical variations may provide an explanation for idiopathic difficulties, chewing or swallowing as a by-product of limited hyoideal mobility.